2018
DOI: 10.1163/22134913-20181093
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Depth Based on Interactions Between Fluorescent and Conventional Colours: A Case Study on Frank Stella’s Irregular Polygons Paintings

Abstract: Although Frank Stella intended to create flat, illusion-less Irregular Polygons paintings, it is not uncommon to experience the illusion of colour depth, based on the interaction between their fluorescent and conventional colours. Some critics praised these artworks’ flatness, while others described odd depth experiences that they categorised as a new kind of illusion. In order to provide a correct reading of these works and to reassess their art historical significance, a scientific case study regarding this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 4 publications
1
9
1
Order By: Relevance
“…For Hiraqla Variation II, only 11.5% of the participants did not experience depth, while 83.5% of the participants did (59% even reported strong depth effects). Note that the fluo yellow and fluo blue areas in Effingham I did not generate any depth effects in this study (in contrast Original Contributions -Originalbeiträge to De Winter et al, 2018), again probably due to the ageing effect of the fluorescence in the real painting here (compared to the freshly screen-printed designs in the previous study).…”
Section: Spatial and Temporal Aspects Of Frank Stella's Work With Col...contrasting
confidence: 47%
See 1 more Smart Citation
“…For Hiraqla Variation II, only 11.5% of the participants did not experience depth, while 83.5% of the participants did (59% even reported strong depth effects). Note that the fluo yellow and fluo blue areas in Effingham I did not generate any depth effects in this study (in contrast Original Contributions -Originalbeiträge to De Winter et al, 2018), again probably due to the ageing effect of the fluorescence in the real painting here (compared to the freshly screen-printed designs in the previous study).…”
Section: Spatial and Temporal Aspects Of Frank Stella's Work With Col...contrasting
confidence: 47%
“…The first study consisted of a controlled experiment with stimuli derived from Frank Stella's Irregular Polygons series (1965)(1966) for which he created 11 shaped canvasses that were each being executed four times in four different colour combinations, some fluorescent and some conventional (De Winter, Moors, Van Gelder, & Wagemans, 2018). With these works, Stella claimed to have found a new kind of illusionism, which is completely abstract and not relatable to any classic form of illusion known from traditional art.…”
Section: Spatial Aspects Of Frank Stella's Work With Colours and Patt...mentioning
confidence: 99%
“…This means subjecting them to a (semi-controlled) study in a wide sample of viewers. This was already done for color depth and fast capturability in two previous laboratory studies ( De Winter et al, 2018, 2020. The first one (De Winter et al, 2018), based on four Irregular Polygon paintings (1966-'67), showed that participants experienced more depth in the fluorescent colors (i.e., perceived them as protruding) than their conventional variants (as the colors appear in reproductions) or the adjacent conventional colors in the same design.…”
Section: General Introductionmentioning
confidence: 99%
“…This was already done for color depth and fast capturability in two previous laboratory studies ( De Winter et al, 2018, 2020. The first one (De Winter et al, 2018), based on four Irregular Polygon paintings (1966-'67), showed that participants experienced more depth in the fluorescent colors (i.e., perceived them as protruding) than their conventional variants (as the colors appear in reproductions) or the adjacent conventional colors in the same design. This finding is inconsistent with Stella's claim (which he first made in the interview with Lane Slate) that his works are experienced as flat and frontal (i.e., have no depth effects) (Slate, 1966).…”
Section: General Introductionmentioning
confidence: 99%
“…Winter et al explores the visual impact of fluorescent colors on Frank Stella's concept of 'instantaneously capturable' paintings [5]. Another study investigates the illusion of color depth experienced in Frank Stella's Irregular Polygons paintings based on the interaction between their fluorescent and conventional colors [6]. However, this study reevaluate Stella's work within the context of abstraction and disruption to 1 Korean Museum of Straw and Life, Seoul, Korea [Curator] e-mail : jin3233@gmail.com 132…”
Section: Introductionmentioning
confidence: 99%